Effectiveness of Learning Model of Gawi Sabumi to Improve Students’ High Order Thinking Skills and Ecological Awareness - Ahmad Suriansyah; Riandy Agusta (TROPICAL WETLAND JOURNAL, 2021)
Learning during the COVID-19 pandemic tends to be less developed students' skills. Based on the facts, many elementary school teachers in South Kalimantan are experiencing difficulties because there are limited models and strategies to implement online learning. This reason encourages developing the innovation blended learning model. Innovation on this study is the the product of developing blended learning model with the syntax are Group, Analysis, Work Together, Inform, Solve the problem on outdoor, Actualization of solution, Battle games, Unity on role play, Manage conclusion and Invent the creation (GAWI SABUMI). The purpose of this study is to produce a new learning model and find out the effectiveness of the GAWI SABUMI learning model to improve the ecological awareness and high order thinking skills of elementary school students in Banjarmasin. This study used the type of research and development consisted of three phases to find the effectiveness of the model on the dependent variable through the quasi-experimental research. The study sample was 40 students on an elementary school in Banjarmasin. The result of quality evaluation of the blended learning model GAWI SABUMI was at a high level (X= 4.62) (SD = 0.14). Students had post-test learning skills scores higher than pre-test at .01 level of significance which means that the GAWI SABUMI model meets the criteria of being valid, reliable, and feasible to be implemented and potential to improve students' high order thinking skills and ecological awareness.